Making Both Ends Meet - Anderberg, Peter (Disability Studies Quarterly, 2005)
The purpose of this article is to launch a new conceptual design tool in rehabilitation engineering, technology, and Disability Studies, useful both as guidance and help for people with disabilities in analyzing their own functional aids, and as inspiration and meta-guidelines for designers. It is non-discriminating and classification-free and differs from a mere classification system like the International Classification of Functioning (ICF). The origin of the tool is twofold: experiences of my own disability and of research in rehabilitation engineering.